Successful Non-Surgical Correction Method For Uterine Torsion In Goats - Balasubramanian, S.; Sathiamoorthy , T.; Raja , S.; Manokaran, S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
In goats, the gravid horn is in the shape of an arc or U-shaped loop with the vagina and ovary at the respective end of the arc. Uterine torsion signifies the rotation of this arc on its transverse axis, though observed in all animals (Noakes et al., 2001), report on its occurrence in goats is scarce. In general, detorsion procedures described include simple rolling of the dam and C-section. In the present communication, a simple non-surgical method, a modified Schaffer’s technique adopted in cattle, for successful correction of uterine torsion in goats is reported.